Vascular Grafts and Flow-through Flaps for Microsurgical Lower Extremity Reconstruction - Toia, Francesca; Zabbia, Giovanni; Roggio, Tiziana; Pirrello, Roberto; D'Arpa, Salvatore; Cordova, Adriana (Journal of Reconstructive Microsurgery, 2017)
Background The use of vascular grafts is indicated in case of insufficient pedicle length or for complex defects involving both soft tissues and vessels. Venous grafts (for both venous and arterial reconstructions) and arterial grafts (arterial reconstruction) can be used. This study retrospectively evaluated the needs for vascular reconstruction and its results in a clinical series of lower limb reconstructions with microsurgical free flaps.Materials and Methods From 2010 to 2015, a total of 16 vascular grafts or flow-through flaps were used in 12 patients out of a total of 150 patients undergoing microsurgical reconstruction (8%). Arterial reconstruction was performed in seven cases (six flow-through flaps, one arterial graft), combined arterial and venous reconstruction in four cases (three vein grafts, one combined venous/arterial graft), and venous reconstruction in one case (one venous graft). The rate of complications and donor-site morbidity related to vascular graft harvest were evaluated.Results Reconstruction was successful in all cases, despite an overall complication rate of 17 and 8% of surgical revision. Donor-site morbidity, subjectively evaluated, was minimal with respect to functional deficits and aesthetic outcome. Indications for the different types of grafts are discussed.Conclusion The use of vascular grafts is needed in a relevant percentage of microsurgical reconstruction cases. Venous and arterial vascular grafts, transient arteriovenous fistulas, and “flow-through” microsurgical flaps showed a safe reconstruction comparable to microsurgical reconstructions without the use of grafts. Donor-site morbidity secondary to vascular graft harvest is minimal, and in almost 70% of cases no additional scars are needed.
Keywords: vascular grafts; lower limb reconstruction; microsurgery